A novel methodology to develop a foot and mouth disease virus (FMDV) peptide-based vaccine in transgenic plants - Dus Santos, María José (2002)
The expression of antigens in transgenic plants has been increasingly used as an alternative to the classical methodologies for antigen expression in the development of experimental vaccines. However, an important limitation in most cases is the low concentration of the recombinant antigens in the plant tissues, which reduces the possibilities of practical applications. Because the site of insertion of the transferred DNA into the cellular chromosomal DNA is at random, different levels of foreign protein expression in independent transformants is expected. Strategies to allow the evaluation of a high number of the transgenic individuals, usually an expensive and very time consuming process, would permit the selection of those plants presenting the highest levels of recombinant protein expression. Here, we present the development of an experimental immunogen based in the expression of a highly immunogenic epitope from foot and mouth disease virus (FMDV) fused to the glucuronidase (gus A) reporter gene, which allows selection of the transgenic plants by the ß-glucuronidase (ßGUS) enzymatic activity. We produced transgenic plants of alfalfa expressing the immunogenic site between amino acid residues 135–160 of structural protein VP1 (VP135–160), fused to the ßGUS protein. Plants expressing the highest levels of the immunogenic epitope VP135–160, analyzed by Western blot, were efficiently selected based on their levels of ßGUS enzymatic activity. The FMDV epitope expressed in plants was highly immunogenic in mice which developed, after immunization, a strong anti-FMDV antibody response against a synthetic peptide representing the region VP135–160, to native virus VP1, and to purified FMDV particles. Additionally, these mice were completely protected against experimental challenge with the virulent virus. To our knowledge, this constitutes the first report of a peptide-based vaccine produced in transgenic plants that induces a protective immune response when used in experimental hosts. Also, these results demonstrated the possibility of using a novel and simple methodology for obtaining transgenic plants expressing high levels of foreign immunogenic epitopes, which could be directly applied in the development of plant-based vaccines.